Technology-Enhanced Project-Based Learning for Developing Numeracy Skills in Elementary Education: A Systematic Literature Review - Dhina Cahya Rohim; Wardono Wardono; Noening Andrijati (Universitas Negeri Semarang, 2026)
Numeracy skills are among the fundamental competencies that need to be developed in elementary school students. With the rapid advancement of digital technology, technology-enhanced Project-Based Learning (PjBL) has emerged as a promising instructional approach to support the development of these skills. This study aims to systematically review existing research on the implementation of technology-enhanced PjBL for developing numeracy skills in elementary education. The study employed a Systematic Literature Review (SLR) methodology following the PRISMA 2020 guidelines. A literature search was conducted in the Scopus database, yielding 623 records. After applying predefined inclusion and exclusion criteria, 23 articles were selected for further analysis. The findings indicate a growing research interest in technology-enhanced PjBL in recent years. The integration of technology within PjBL was found to positively influence students’ numeracy skills, conceptual understanding of mathematics, problem-solving abilities, critical thinking, and learning engagement. However, several challenges remain, including limited technological infrastructure, teachers’ digital competencies, and the management of project-based activities. In conclusion, technology-enhanced PjBL demonstrates significant potential for supporting the development of numeracy skills among elementary school students and warrants further exploration in both educational practice and future research.